Model GI-GI: Sistem Pembelajaran Active Learning Berbasis Student Centred Menggunakan Pendekatan Scientific Approach dalam Rangka Mewujudkan Tujuan ke Empat SDGs - Ade Putra (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2022)
One of the goals of the Sustainable Development Goals is quality education and to achieve quality education, of course, it starts with a good and quality learning system. One of the problems that have always arisen in the learning process is about learning models or specifically about teaching methods, one of which is that the learning process is dominated by conventional learning models or learning methods as the mainstay method. This learning method is considered less effective in improving students' ability to think critically and creatively. In this article, we will discuss one of the learning models that are considered to have an important role in improving the quality of education in Indonesia, namely the GI-GI learning model, a combination of the Group Investigation and Guided Inquiry learning models. This model is considered to be more effectively applied to students because it is able to create students who can think critically and creatively so that they can create good quality education and help realize the four goals of the SDGs, namely Quality Education.